Prevalence of insufficient physical activity in children from public schools - Michelle da Costa Mata; Ruth Minamisava; Karla Regina Inácio Vaz Lauriano; Gabriela Moreira Policena; Priscila Valverd de Oliveira Vitorino; Maria Aparecida da Silva Vieira (Universidade Estadual de Maringá, 2018)
This study aimed to identify the prevalence of physical inactivity (PI) in schoolchildren of both sexes enrolled in public elementary schools in Goiânia (State of Goiás). A cross-sectional, analytical study with 482 schoolchildren aged six and seven. Those responsible answered a form containing sociodemographic variables, data related to the practice of physical activity (PA) and displacement to school. Children who didn't perform at least 60 minutes of PA per day were considered physically inactive. Descriptive analyses and chi-square statistics were used for the differences in proportions. The prevalence of PI was 31.9% (95% CI: 27.9-36.2), higher in the female students (37.6 - 95% CI: 31.8 to 43.7) compared to the male students (25.6 - 95% IC: 20.2 to 31.5) (p = 0.004). There was no difference in prevalence between inactive children from families enrolled or not in the Family Health Strategy (FHS) (p = 0.969). The prevalence of PI was high among schoolchildren, with a difference between the sexes. Being enrolled in the FHS didn't change the prevalence of PI, indicating that the actions of health teams in schools need to be re-evaluated. These results indicate the need for programs to encourage the practice of PA among schoolchildren.